Nationwide patterns of cataract surgery in Japan: facility-level volume and outpatient versus inpatient procedures using the National Database of Health Insurance Claims (NDB) - Susumu Kunisawa; Yuichi Imanaka (Japanese Journal of Ophthalmology, 2026)
Abstract Purpose Cataract surgery is among the most commonly performed types of surgery in Japan, but the actual surgical volume at the healthcare facility level remains unclear. This is partly because a substantial number of cataract surgical procedures are performed in clinics, making comprehensive investigation of relevant data difficult. This study used the National Database of Health Insurance Claims (NDB) to elucidate the number of surgical procedures, including outpatient procedures, performed at the facility level. Study design Retrospective observational study. Methods Using NDB data, we determined the number of cataract surgical procedures performed at the facility level over a 9-year period (fiscal years 2016–2024). We also analyzed the proportion of procedures performed in outpatient settings. Results Approximately 4,500 facilities performed cataract surgery each year, with the number of facilities increasing. Although variations were observed across prefectures, no systematic regional patterns emerged. In most regions, facilities typically performed 100–300 procedures per year. Many facilities operate entirely at outpatient settings, while others operate entirely at inpatient settings. Facility-level outpatient practice patterns varied substantially across procedure-volume categories. This descriptive pattern was observed across the 9-year period. Conclusions These nationwide facility-level data provide an important baseline for understanding cataract surgery practice in Japan. These findings may support future research and health policy discussions on cataract surgery practice across healthcare facilities.